1998
DOI: 10.1159/000026514
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Effects of Caffeine on Performance, Mood, Headache, and Sleep

Abstract: Despite being the most widely consumed psychoactive substance in the world, there is considerable confusion regarding the effects of caffeine. This study examined objective indices of performance, and self-reported mood, headache, and sleep in 36 healthy male and female habitual caffeine consumers exposed to a pattern of moderate intake. A double-blind placebo-controlled cross-over design with counterbalancing was employed in which all subjects participated in four experimental conditions involving the ingesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
175
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(188 citation statements)
references
References 38 publications
12
175
1
Order By: Relevance
“…The reported effect of caffeine on psychomotor function is somewhat conflicting (21,24,35), but, in this study, there was no indication that caffeine improved either reaction or movement times. The frequency of withdrawal symptoms (20,22,40) and side effects (21, 24) associated with caffeine, as well as the impaired postural stability (10,41), are in accordance with previous findings. Thus in one study by Franks et al (10), body sway was significantly increased in the young subjects 40 min after ingesting 4.3 mg/kg caffeine, and also elderly subjects in a study by Swift and Tiplady (41) showed an increased body sway on caffeine compared with placebo.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The reported effect of caffeine on psychomotor function is somewhat conflicting (21,24,35), but, in this study, there was no indication that caffeine improved either reaction or movement times. The frequency of withdrawal symptoms (20,22,40) and side effects (21, 24) associated with caffeine, as well as the impaired postural stability (10,41), are in accordance with previous findings. Thus in one study by Franks et al (10), body sway was significantly increased in the young subjects 40 min after ingesting 4.3 mg/kg caffeine, and also elderly subjects in a study by Swift and Tiplady (41) showed an increased body sway on caffeine compared with placebo.…”
Section: Discussionsupporting
confidence: 91%
“…The rather low rate of perceived exertion, together with a median working rate of 50 W and a low working intensity in relation to V O 2 max , raises the question of what caused the participants to stop the endurance test? Was the increase in endurance with caffeine due to an increased ability to continue working, or was it rather a psychological effect of caffeine in way of reducing tiredness and increase alertness (20,35)? The large interindividual variability in cycling endurance time could be due to the variation in habitual physical activity, ranging from 0 to 10 h weekly, or that the study group was allowed minor disabilities as hypertension and asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine was found to either (1) exert no effects on free recall performance in sixteen studies [7][8][9]11,[21][22][23][24][25][26][27][28][29][30][31][32]; (2) improve recall in six studies [33][34][35][36][37][38]; or (3) impair recall in three studies [8,12,39].…”
Section: Short Term Memorymentioning
confidence: 99%
“…The overbearing presence of coffee establishments such as Starbucks and Dunkin' Donuts are enough to illustrate that society has become dependent on caffeinated beverages. Caffeine is a known stimulant that people utilize to increase alertness and wakefulness (James, 1998). Moreover, caffeine has been shown to improve functional and cognitive performance (Smith, Maben, & Brockman, 1993;Sun, Zhang, He, Liu, & Miao, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus it is essential to consider both the positive and negative effects of this substance. Although research has not shown that caffeine has any significant causal relationship with mood (Smith et al, 1993), several studies have found that the intake of caffeine before bed delays sleep onset time, decreases total sleep time, and reduces sleep quality (Goldstein, 1963;James, 1998;Smith et al, 1993;Wright, Badia, Myers, Plenzler, & Hakel, 1996). Further research should be conducted in order to reveal whether these effects on sleep cause negative consequences for performance and behavior.…”
Section: Introductionmentioning
confidence: 99%